Assessment of population immunity to measles in Ontario, Canada: a Canadian Immunization Research Network (CIRN) study. Issue 12 (2nd December 2019) - Bolotin, Shelly; Severini, Alberto; Hatchette, Todd; McLachlan, Elizabeth; Savage, Rachel; Hughes, Stephanie L.; Wang, John; Deeks, Shelley L.; Wilson, Sarah; Brisson, Marc; Halperin, Scott A.; Gubbay, Jonathan; et al.
ABSTRACT: Canada eliminated measles in 1998. We conducted a sero-epidemiology study to estimate population immunity to measles in the province of Ontario, Canada and to identify groups at higher risk of outbreaks. We used a previously developed modified enzyme immunoassay to test 1, 199 residual sera from patients aged 1–39 years. We re-tested negative and equivocal sera using a plaque reduction neutralization assay. We interpreted our results in the context of Ontario's immunization program and vaccine coverage data. Of 1, 199 sera, 1035 (86.3%, 95% confidence interval (CI) 84.4, 88.2) were above the measles threshold for protection, 70 (5.8%, 95% CI 4.5, 7.2) were equivocal and 94 (7.8%, 95% CI 6.3, 9.4) were negative. The proportion of positive sera was highest for those 1–5 years, with 180/199 (90.5%, 95% CI 86.4, 94.5) positive sera, and lowest for those age 12–19 years, at 158/199 (79.4%, 95% CI 73.8, 85.0). Adjusted for age, females were more likely than males to have antibody titers above the threshold of protection (odds ratio = 1.60, 95% CI 1.14, 2.24). Most of the study cohort were eligible for two measles vaccine doses, and vaccine uptake in Ontario is >90% for school-aged cohorts. We observed a higher than expected proportion of sera with antibody levels below the threshold of protection, suggesting that immunity in some Ontario age-groups may be waning, despite high vaccine coverage. Alternatively, the traditional measles correlates of protection may not be an appropriate measure of population protection in measles-eliminated settings.